The Effect Interacting of Chitosan as a Biofilm with Nisin on the microbial content Chicken Breast Meat Preserved in Cold Storage (NTU Journal of Agriculture and Veterinary Science, 2024)
This study aims to evaluate the effectiveness of the chitosan (ch) and nisin (Ni) composite films on chicken breast meat's microbial content during storage at four °C for 28 days. The results indicated that adding nisin to chitosan increased the inhibitory diameter of Gram-negative and positive bacteria compared to chitosan and nisin alone. Microbial tests of chicken breasts included estimating the total number of all aerobic bacteria, proteolytic Bacterial Count and lipolytic Bacterial Count, the composite films of chitosan -nisin performed better than those of chitosan alone and on the control samples because they revealed a drop in all bacteria during the preservation periods. The addition of nisin to the chitosan casings increased the water vapour (vapor) permeability.